Aktivitas Sitotoksik dan Profil Kromatogram Daun Sirsak (Annona muricata L.) yang Diiradiasi - ERMIN KATRIN; RHILA AMALIAH; ZUHELMI AZIZ; HENDIG WINARNO (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Soursop (Annona muricata L.) is one of plants included in Annonaceae which the leaves has cytotoxic activity on cancer cells. Preservation efforts of soursop leaves is carried out by gamma irradiation technic. This research aimed to study the effect of gamma irradiation on the bioactivity and chromatogram profiles of the active fraction from soursop leaves.Dry powders of soursop leaves were irradiated using gamma with doses of 5; 7.5; 10; and 15 kGy and repeated twice, respectively for certain doses. Then each sample was macerated with n-hexane, ethyl acetate and ethanol gradiently. Each extract was tested against leukemia L1210 cells. Ethyl acetate extract was the most active (IC50= 7.36 µg/mL) compared with n-hexane (20.18 µg/mL) and ethanol extract (13.89 µg/mL). Ethyl acetate extracts was fractionated using column chromatography obtained ten fractions. The result of cytotoxic activities assay of ten fractions were obtained that fraction 8 was the most active with IC50 value of 0.45 µg/mL. Cytotoxic activity of fraction 8 from irradiated samples showed that gamma irradiation decreased cytotoxic activity of fraction 8, but they were still active (IC50 < 20 µg/mL). Analysis and identification of fraction 8 by the HPLC and TLC-densitometry showed that there were broad peak which decreased in the irradiated samples.The maximum radiation dose for soursop leaves without damaging its bioactivity and that did not change the chromatogram profilesis 7.5 kGy.